2022
DOI: 10.3389/fonc.2022.714663
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylated CDO1 and ZNF454 in Cytological Specimens as Screening Biomarkers for Endometrial Cancer

Abstract: We aimed to estimate the diagnostic value of DNA methylation levels in cytological samples of endometrial cancer (EC) and atypical hyperplasia (AH). Two hypermethylated genes, namely, cysteine dioxygenase type 1 (CDO1) and zinc finger protein 454 (ZNF454), in patients with EC were identified from The Cancer Genome Atlas database. In 103 endometrial histological specimens (the training set), the methylation levels of candidate genes were verified by quantitative methylation-specific polymerase chain reaction (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…of 0.83 and 0.90, respectively. In line with previous studies,17,24,32 CDO1 allowed endometrial cancer detection with excellent performance in all sample types tested (AUC 0.90-0.96). HAND2 performed moderately in all sample types (AUC 0.62-0.71), as opposed to previously described performances of 0.91 and 0.96 in vaginal swabs of stage IA and stage IB/II/III patients, respectively.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…of 0.83 and 0.90, respectively. In line with previous studies,17,24,32 CDO1 allowed endometrial cancer detection with excellent performance in all sample types tested (AUC 0.90-0.96). HAND2 performed moderately in all sample types (AUC 0.62-0.71), as opposed to previously described performances of 0.91 and 0.96 in vaginal swabs of stage IA and stage IB/II/III patients, respectively.…”
supporting
confidence: 90%
“…Finally, this comparative study had no access to paired samples from controls and did not include controls with postmenopausal bleeding symptoms or benign endometrial conditions. Even though others have shown that most of the markers tested in our study enable discrimination between benign endometrial pathology and cancer 17,18,20,21,23,24,32 , this was not validated in the current study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Similarly, previous reports documented 3-gene panel (BHLHE22-CDO1-CELF4/BHLHE22-CDO1-TBX5) or single gene-based (PCDHGB7) DNA methylation for EC detection using cervical scrapings, the ROC for these markers ranged from 0.80 to 0.94, or 0.86, respectively. 11 13 Also, Wang et al 26 reported a relevant study on methylation marker-based EC screening in endometrial cytological samples using Li Brush. Compared with endometrial sampling, cervical Pap brush sampling is a more acceptable screening tool for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the use of DNA methylation testing in cervical cytology samples shows promise for the diagnosis of EC and AH. Two hypermethylated candidate genes, namely, cysteine dioxygenase type 1 (CDO1) and CUGBP Elav-like family member 4 (CELF4), have been identified as potential biomarkers for endometrial cancer (33,(37)(38)(39). As a key enzyme in cysteine catabolism, CDO1 belongs to the non-heme Fe(II) dioxygenase family.…”
Section: Introductionmentioning
confidence: 99%